Pembuatan Marmalade jeruk Bali (Kajian Proporsi Daging Buah : Albedo dan Penambahan Sukrosa) (Jurnal Teknologi Pangan, 2008)
Pembuatan Marmalade jeruk Bali (Kajian Proporsi Daging Buah : Albedo dan Penambahan Sukrosa)